KETIMPANGAN GENDER DI BALI: ANALISIS BUDAYA PATRIARKI, PERAN ADAT DAN AGAMA, SERTA RELEVANSINYA DI DUNIA MODERN - Galuh Anissa Sekar Ayu; Putra Ardiansyah; Royhan Ahmad Danarlie (Pusat Studi Gender dan Anak (PSGA), Universitas Islam Negeri Syarif Hidayatullah, 2022)
Abstract. This research is motivated by the patriarchal culture that is strongly embedded in the Balinese cultural system. The patriarchal culture that penetrates into the life of the Balinese people is predicted to be the biggest cause of gender inequality in various areas of people's lives. Gender inequality in the province of Bali can be found in the social, economic, cultural, political, and demographic fields. The main objective of this research is to provide answers to the formulation of the problem